Haematological values of Nigerian goats and sheep - Oduye, O.O. (1976)
Studies the haematological parameters of clinically healthy goats and sheep in Ibadan, west state of Nigeria. Eighty-five goats from West African Dwarf goat, the Sokoto, Kano Brown goat and their crosses; and 295 sheep from the West African Dwarf sheep of ages ranging from 2 weeks to 7 years were investigated. Most values in the goats were similar to those reported for temperate breeds of goats although the haemoglobin concentration and the MCHC were lower. The haematocrit, haemoglobin concentrations and red cell counts of West African Dwarf sheep were lower while the MCV were higher than those for sheep in the temperate climate. RBC values decreased with age in both Nigerian goats and sheep. Although sex and pregnancy appeared to have little or no influence on the erythrocytic values, pregnant ewes had higher haematocrit and haemoglobin values. The low erythrocytic values were attributed to a low but constant parasitic burden which affected the flock. Total leucocyte counts were considerably higher in the Nigerian goat and sheep than those of temperate breeds of animals. Young goats had higher total leucocyte count while pregnant goats had reduced leucocyte counts. The leucocytic values were not affected by age and sex. Pregnant ewes also had higher leucocyte counts than non-pregnant ewes and rams.